Analysis of Cryptographic Randomness Properties of a TRNG-based Key Generator Hardware - Durmus, Beyzanur; Ozkaynak, Fatih (Institute of Electrical and Electronics Engineers Inc., 2022)
One of the criteria that can emphasize the importance of cryptological key generators can be related to the number of commercial products and market size in this field. One of these products is Crowd Supply Infinite Noise TRNG hardware. In this study, the cryptographic features of this hardware have been analyzed and its suitability for practical information security applications has been examined. Analyzes have been carried out using the NIST SP 800-22 Statistical Test Suite, which is one of the widely accepted analysis tools in this field. Analysis results revealed that more care should be taken when using information security equipment. © 2022 IEEE.
16th IEEE International Conference on Advanced Trends in Radioelectronics, Telecommunications and Computer Engineering, TCSET 2022 -- 22 February 2022 through 26 February 2022 -- Lviv-Slavske -- 179157
Keywords: NIST; random number generator; security hardware; TRNG